Islamic Perspectives on Multicultural Education Values in The Sumberdem Clean Village Tradition - Syahriyah, Ummi Ulfatus; Aziza, Ilma Fahmi; Islahuddin, Islahuddin (UIN Maulana Malik Ibrahim Malang, 2024)
Multiculturalism emerges as a force promoting diversity within the global system, driving the creation of true social justice. However, this concept is not universally accepted; some people reject it, viewing it as obscuring the essence of religion. This research aims to describe the values of multicultural education embedded in the Clean Village tradition in Sumberdem Village, examining them from the perspective of Islamic teachings. The research employs a qualitative method with a phenomenological approach. Data collection involved in-depth interviews, observations, and documentation, followed by interpretive phenomenological analysis. The findings reveal that the multicultural values expressed in the Clean Village tradition include social care, consensus, mutual cooperation, respect for diversity, and fairness. These values align harmoniously with Islamic teachings, offering solutions to humanitarian challenges by weaving diversity into a cohesive social fabric. This process shapes a well-rounded individual who balances their roles as abdullah (God’s servant) and khalifatullah (God’s steward). This tradition can serve as a model for integrating multicultural values into community practices, especially in diverse cultural and religious settings, fostering inclusive environments that promote mutual respect and collective well-being, in alignment with both secular and religious frameworks for social harmony. Multikulturalisme muncul sebagai kekuatan yang mendorong keragaman dalam sistem global, yang menggerakkan terciptanya keadilan sosial sejati. Namun, konsep ini tidak sepenuhnya diterima secara universal; beberapa orang menolaknya karena dianggap mengaburkan esensi agama. Penelitian ini bertujuan untuk menggambarkan nilai-nilai pendidikan multikultural yang terkandung dalam tradisi Bersih Desa di desa Sumberdem, kemudian mengkajinya dari perspektif ajaran Islam. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologis. Pengumpulan data melibatkan wawancara mendalam, observasi, dan teknik dokumentasi, yang diikuti dengan analisis fenomenologis interpretatif. Hasil penelitian menunjukkan bahwa nilai-nilai multikultural dalam tradisi Bersih Desa meliputi kepedulian sosial, musyawarah, gotong royong, penghormatan terhadap keragaman, dan keadilan. Nilai-nilai ini selaras dan harmonis dengan ajaran Islam, yang menawarkan solusi atas tantangan kemanusiaan dengan merajut keragaman menjadi ikatan sosial yang utuh. Proses ini membentuk manusia yang seimbang dalam peran sebagai abdullah (hamba Allah) dan khalifatullah (wakil Allah). Tradisi ini dapat menjadi model untuk mengintegrasikan nilai-nilai multikultural dalam praktik komunitas, terutama di lingkungan dengan latar belakang budaya dan agama yang beragam, serta memupuk lingkungan inklusif yang mendukung saling menghormati dan kesejahteraan bersama, selaras dengan kerangka sekuler dan religius untuk harmoni sosial.